2016
DOI: 10.5130/ccs.v8i2.4969
|View full text |Cite
|
Sign up to set email alerts
|

People Seeking Asylum in Australia and their Access to Employment: Just What Do We Know?

Abstract: Public and political claims about the employment of people from a refugee background in Australia do not always reflect the research findings in this area. For example, recent claims by a senior Coalition Government Minister about people seeking asylum who arrived to Australia by boat during the previous Labor Government's terms in office posit that many have limited employment prospects. However, given there is little research or government reporting on the experiences of asylum seekers who arrived during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…As the first survey of the population of humanitarian migrants in Australia, the BNLA data is unique. Most studies in Australia and other countries have used a relatively small, and often non-random, sample of a specific ethnic group (Fleay et al 2016), or used general-purpose survey data, which was not representative of humanitarian migrants (Hugo 2013). Our findings may not be generalized to other countries due the inter-country differences in immigration/refugee and welfare policies, geopolitical circumstances, geographical locations and so on that contribute to systematic differences in the populations of humanitarian migrants.…”
Section: Discussion and Future Researchmentioning
confidence: 85%
“…As the first survey of the population of humanitarian migrants in Australia, the BNLA data is unique. Most studies in Australia and other countries have used a relatively small, and often non-random, sample of a specific ethnic group (Fleay et al 2016), or used general-purpose survey data, which was not representative of humanitarian migrants (Hugo 2013). Our findings may not be generalized to other countries due the inter-country differences in immigration/refugee and welfare policies, geopolitical circumstances, geographical locations and so on that contribute to systematic differences in the populations of humanitarian migrants.…”
Section: Discussion and Future Researchmentioning
confidence: 85%
“…Higher levels of discrimination are associated with lower levels of life satisfaction, which is a push factor in the decision to relocate (Han and Humphreys, ; Griffiths et al., ; Houle and Schellenberg, ). Refugees identify negative stereotyping and prejudices on the part of employers as barriers to their participation in local labour markets (Fleay et al., ). Such representations of refugees devalue their skills, as they feel forced into undesirable “refugee jobs” within the host country's labour market (Jackson and Bauder, ).…”
Section: Labour Market Integration and Retentionmentioning
confidence: 99%
“…Australia's immigration policy has a preference for refugees who are most likely to be able to assimilate into Australia; this includes gaining employment and education (Colic‐Peisker, ). This, alongside research that highlights the skills, drive, and entrepreneurship that are brought to a new country by refugees, suggests that the presence of refugees result in long‐term economic and social benefits to a community (Fleay, Lumbus, & Hartley, ). An investigation of educational achievement of refugees arriving in Australia in 1999/2000 found that, although level of education differs between countries, overall, one third of refugees have a tertiary qualification, another third having completed high school (Forrest et al, ).…”
Section: Resultsmentioning
confidence: 99%